IMPLEMENTASI FTP SERVER DENGAN METODE TRANSFER LAYER SECURITY UNTUK KEAMANAN TRANSFER DATA MENGGUNAKAN CENTOS 5.8 - Bagus Satria Pradana; Reza Pahlevi; Bowo Sumarjono (STMIK Mardira Indonesia, Bandung, 2018)
Information needed in life, to get information and exchange information needed is easy to do anytime and anywhere. File and data information, computer network is one of the important things for transfer information. One of the media that can be used is FTP (File Transfer Protocol), an application to exchange data between clients and servers on a network, by means of clients uploading files stored on the server hard disk and accessible through clients connected to the internet network.Through the development of current technology, important files that are uploaded and downloaded are very vulnerable to the world of the internet such as the wireshark tool that can be read username, password, and files that are uploaded and downloaded by the client. Therefore an FTP server was created with a data transfer security system. FTP servers that have activated the TLS (Transfer Layer Security) feature can provide user name information, passwords, and files that are uploaded and downloaded by the client that cannot be read by the Wireshark tool.In full capacity, use the hard disk server, then use the Quota Disk used to provide the client quota in uploading. Thus, FTP servers that have not used TLS are user names, passwords and files can be read by the Wireshark tool. While FTP servers that have used TLS are safer because of user names, passwords and files not read by the Wireshark toolKeywords:Disk Quota, File Transfer Protocol, (TLS) Transfer Layer SecurityDOI 10.5281/zenodo.3373760